'A Very Modern Kind of English Loneliness': John Redwood, the Welsh Office and Devolution. (1st December 2019) - Gooberman, Leon
John Redwood was appointed Secretary of State for Wales in 1993. He pursued a radical right- wing agenda for two turbulent years before resigning to unsuccessfully challenge John Major for the premiership. This article examines this period to make two arguments. One is that Redwood's imposition of a morally-charged Thatcherite agenda challenged and inadvertently discredited the Conservatives and the institutions through which they governed. This loss of credibility then enabled his opponents to magnify pre-existing discontent and secure a narrow victory in the 1997 devolution referendum. The other argument is that Redwood's period in Wales demonstrates the counterproductive potential of ideological dedication. His plan to overthrow the prime minister failed, he damaged his party and he helped facilitate devolution, outcomes that were the opposite of his intentions.